Study on the limiting height of rooftop solar energy equipment in street canyons under the cityscape constraints. (August 2020) - Xu, Luting; Long, Enshen; Wei, Jincheng
Highlights: A new solution of visual pollution from rooftop equipment was put forward. The model of equipment limiting height in urban street canyons were established. Equipment limiting height is effected by 5 factors, roof height, street width, etc. There is a proportional relation between equipment limiting height and roof height. The equipment limiting height is inversely proportional to the street width. Abstract: The random installation of various solar energy equipment on building roofs has caused visual damage to the cityscape. Keeping the rooftop equipment out of sight of the pedestrians is a new solution to eliminate visual pollution. Based on the complex urban street canyons, this paper describes a physical and mathematical model relating to the limiting height of equipment installations at any position on the roof. It is found that the limiting height of equipment varies with the building roof height, the street width, and other factors. In addition, for a case with four main urban roads, the variation patterns for the limiting height of rooftop equipment changed with the street width and the distance from the installation to the parapet have been established, which is of great relevance for determination of the limiting equipment height in actual installations. The research can not only help to remove visual pollution from rooftop equipment in street canyons, and provide a guide for the selection and installation of solar equipment, but can also provide significant information for urban space planning and building design.